Integral Waste Management in Primary Health Care Centers of the Secretary of Health in México: a case study - Ocampo Escobedo, Rosa Llisel; Ortiz-Chacha, Christian S.; Risso Günther, Wanda María; Azamar Arismendi, Rosa Aurora (Horizonte Sanitario, 2021)
Objective: This paper aims to describe waste management in primary health care centers of the Secretary of Health in the municipality of Xalapa, Veracruz, Mexico, as a model case for developing countries. Material and methods: A observational, descriptive and cross-sectional study was conducted. The sample was made up of the seven primary healthcare centers of the Secretary of Health located in the municipality of Xalapa, Veracruz, México. Data collection was carried out with a checklist designed according to the current legislation for the primary health care centers. Results: The global percentage of compliance was 55%, with variation between 47% and 63%. The stage of identification, separation and packaging recorded the highest percentage of compliance, while the temporary storage showed a lower percentage. Conclusion: The waste management in primary health care centers resulted in a level of compliance ranging from low to medium, which suggests the need for specific actions in order to improve waste management in health centers. Keywords: waste management; primary health care; medical waste; Public Health; Mexico